DIPLOMASI INDONESIA TERHADAP UNESCO DALAM MENJADIKAN PENCAK SILAT SEBAGAI WARISAN BUDAYA TAKBENDA - Salma Alysha Sudarsono; Ahmad Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study describes the process and path of Indonesia’s diplomacy towards UNESCO to formalize Pencak Silat as an Intangible Cultural Heritage of Indonesia. The discussion includes a description of the activities carried out by the actors since the process of preparing the dossier, until it was determined by UNESCO. The nomination process is carried out through the Secretariat of Intangible Cultural Heritage and is included in the category of a representative list, because this tradition is still alive and thriving in the lives of Indonesian people.The Constructivism perspective used in this study views that identity and culture are relevant categories in understanding contemporary international relations, as well as being the main factor in understanding the relations and policies at the international level with their dynamic nature. This study uses the theory of Multi-track diplomacy and the concept of Intangible Culture. Descriptive qualitative method is used to examine various government and non-government efforts that collaborate together in the success of the official determination of the tradition of pencak silat by UNESCO. The data was collected through a review of related documents, websites, literature studies, and videos.From 9 to 14 December 2019, the UNESCO Intangible Cultural Heritage Committee held a meeting located in Bogota, Colombia. A total of 24 member countries of the committee discussed about six nominations in the Need of Urgent Safeguarding nominations, 42 Representative List nominations and three Register of Good Safeguarding Practices proposals in the session. In its effort to nominate pencak silat to UNESCO, there are two diplomatic channels used by Indonesia, namely the government route (track one) and the non-government route (track two). The collaboration between the government, the community or local communities is the key to the success of proposing the tradition of pencak silat as a UNESCO Intangible Cultural Heritage. Keywords: Tradition of Pencak Silat, Intangible Culture, Multi Track Diplomacy